Promotion, Brand Image, Brand Awareness on The Intention To Use Service Business Infobarkasbontang - Mulyawan, Nafiri Cholish; Hapsari, Raditha Dwi Vata (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – To analyze the effects of promotion, brand image, and brand awareness on purchase intention in the Infobarkasbontang business. Design/Methodology/Approach – This study employed a quantitative research approach using purposive sampling. A total of 100 respondents were selected, and data were collected through online Likert-scale questionnaires distributed via Infobarkasbontang’s Instagram account. The data were analyzed using validity and reliability tests, multiple linear regression, t-test, and F-test with SPSS version 21. Findings – The results indicate that promotion, brand image, and brand awareness have a positive effect on consumers’ purchase intention. Improving promotional activities, strengthening the brand image, and increasing brand awareness are associated with higher consumer intention to use the brand.   Originality/Value This research provides value by empirically analyzing the combined influence of promotion, brand image, and brand awareness on purchase intention within a social-media-based service business, offering insights that support more effective digital marketing strategies.